A set of polymorphic microsatellite loci for Vriesea gigantea and Alcantarea imperialis (Bromeliaceae) and cross-amplification in other bromeliad species - Palma-Silva, C.; Cavallari, M. M.; Barbara, T.; Lexer, C.; Gimenes, M. A.; Bered, F.; Bodanese-Zanettini, M. H. (Blackwell Publishing, 2007)
Fifteen polymorphic microsatellite markers were isolated and characterized in two species of Bromeliaceae: Vriesea gigantea and Alcantarea imperialis. The number of alleles observed for each locus ranged from three to 16. The loci will be used for studies of the genetic structure of natural populations, reproductive biology, and evolutionary relationships among and within these genera. A cross-amplification test in 22 taxa suggests that the markers will be useful for similar applications in numerous other bromeliad species.
Keywords: Alcantarea; Atlantic Rain Forest; Bromeliaceae; cross-amplification; microsatellites; Vriesea